School Violence: Causes, Consequences and Trauma-Informed Practices - Birdot, Claudia (Social Issues, Justice and Status Series, 2024)
Intro -- Contents -- Preface -- Chapter 1 -- The Causes and Consequences of School Violence: A Review* -- Executive Summary -- Review of Systematic Reviews -- Predictors of School Violence Perpetration -- Predictors of School Violence Victimization -- Consequences of School Violence Perpetration -- Consequences of Violent Victimization at School -- Review of Recent Research -- Conceptualization of School Violence -- Serious School Violence -- Research Funded by NIJ's Comprehensive School Safety Initiative -- Research Gaps and Needs -- Introduction -- Overview of School Violence -- Review of Systematic Reviews -- Predictors of School Violence Perpetration and Victimization -- Results: Predictors of School Violence Perpetration -- Results: Predictors of School Violence Victimization -- Summary of Results: Predictors of School Violence Perpetration and Victimization -- Consequences of School Violence Perpetration and Victimization -- Results: Consequences of School Violence Perpetration -- Results: Consequences of School Violence Victimization -- Summary of Results: Consequences of School Violence Perpetration and Victimization -- Review of Recent Research -- Conceptualization and Measurement of School Violence -- What Recent Research Reveals About Serious School Violence -- Research Funded by NIJ's Comprehensive School Safety Initiative -- Summary of Reviews -- Research Gaps and Needs -- References -- Appendix A. Methods Used To Conduct the Report -- Review of Systematic Reviews -- Review of Recent Research -- Appendix B. Summary of Recent Research Findings -- About the Authors -- Chapter 2 -- The Importance of Trauma-Informed Practices in Education to Assist Students Impacted by Gun Violence and Other Adversities*.